Zoroastrian religion and the importance of the Bible “AVESTO” (Zien Journal of Social Sciences and Humanities, 2022)
When the Zoroastrian religion, based on the belief of the only deity in Movarounnahr, Iran, Khorasan, was adopted, the construction of a special temple-ceasefire, in which the Ahura Mazda cult sanctuaries were located in the cities and villages of these territories, was in full swing